(NzARUBEVNAQ HOROWAQ LITERATURAs (NwYPUSK TWTOROJ(B.s - (Nd(B.(NlOK[IN(B.s ((NmOSKWA s (NmZUYKAs, 1966)
(NiOSIF gAJDIN RODILSQ (B31 (NMARTA (B( 1 (NAPRELQ(B) 1732 (NGODA W AWSTRIJSKOJ DEREW[KE rORAU(B.s
Keywords: (NsME[ANNYE HORYs